2016
DOI: 10.1016/j.neuropsychologia.2015.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Anodal-tDCS over the human right occipital cortex enhances the perception and memory of both faces and objects

Abstract: Accurate face processing skills are pivotal for typical social cognition, and impairments in this ability characterise various clinical conditions (e.g., prosopagnosia). No study to date has investigated whether transcranial direct current stimulation (tDCS) can causally enhance face processing. In addition, the category-and the process-specificity of tDCS effects, as well as the role of the timing of neuromodulation with respect to the execution of cognitive tasks are still unknown. In this single-blind, sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 68 publications
5
63
3
Order By: Relevance
“…However, the typical current amplitude and polarity that resulted in activation was −5 µA or, in some cases, a second application of current. These results parallel human tDCS experiments wherein amounts of current applied are enough to produce behavioral changes after stimulation with very subtle, if any, effects during current application and with reports that more than one administration of tDCS enhance behavioral outcomes 35,36. We found that the threshold current to induce changes in the response to light stimuli in the isolated retina-eyecup was nearly a 1,000-fold less than the 2 mA currents typically administered in human tDCS studies.…”
Section: Discussionsupporting
confidence: 85%
“…However, the typical current amplitude and polarity that resulted in activation was −5 µA or, in some cases, a second application of current. These results parallel human tDCS experiments wherein amounts of current applied are enough to produce behavioral changes after stimulation with very subtle, if any, effects during current application and with reports that more than one administration of tDCS enhance behavioral outcomes 35,36. We found that the threshold current to induce changes in the response to light stimuli in the isolated retina-eyecup was nearly a 1,000-fold less than the 2 mA currents typically administered in human tDCS studies.…”
Section: Discussionsupporting
confidence: 85%
“…Reis and Fritsch (2011) suggest that stimulation is most effective when delivered during the processing of task-relevant information. However, there is also evidence that performance is most improved after stimulation is over (Barbieri et al, 2016). More data are needed to determine whether performing tasks during stimulation results in longer lasting effects of tDCS.…”
Section: Tdcs Can Last a Long Timementioning
confidence: 99%
“…Ruffman et al, 2008), and c) prior work showing that social processing (including emotion perception) can be improved following tES in young adult participants (e.g. Santiesteban et al, 2012Santiesteban et al, , 2015Hogeveen et al, 2014Hogeveen et al, , 2016Janik et al, 2015;Romanska et al, 2015;Barbieri et al, 2016;Liepelt et al, 2016;Sellaro et al, 2016). Indeed, in other domains (e.g.…”
Section: Introductionmentioning
confidence: 98%